1999
DOI: 10.1037/0096-1523.25.4.1162
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of information to the left of the fixated word in reading.

Abstract: The effects of neighborhood size ("N")--the number of words differing from a target word by exactly 1 letter (i.e., "neighbors")--on word identification was assessed in 3 experiments. In Experiments 1 and 2, the frequency of the highest frequency neighbor was equated, and N had opposite effects in lexical decision and reading. In Experiment 1, a larger N facilitated lexical decision judgments, whereas in Experiment 2, a larger N had an inhibitory effect on reading sentences that contained the words of Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 25 publications
(49 reference statements)
9
72
2
1
Order By: Relevance
“…Moreover, the finding that both regressive and progressive saccades were affected by text to the left of fixation makes it unlikely that these influences depend on leftward shifts of attention when reading. In contrast, the influences of text to the left of fixation that have been reported by other researchers may suggest that those influences occur only when a greater allocation of attention has been made to the left, and so occur with regressive saccades (Apel et al, 2012) and word skipping (Binder et al, 1999). Thus, while some aspects of eye movement behavior are associated with shifts in attention, the influence of leftward interword spaces that we observed in our study does not appear to rely on such shifts.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, the finding that both regressive and progressive saccades were affected by text to the left of fixation makes it unlikely that these influences depend on leftward shifts of attention when reading. In contrast, the influences of text to the left of fixation that have been reported by other researchers may suggest that those influences occur only when a greater allocation of attention has been made to the left, and so occur with regressive saccades (Apel et al, 2012) and word skipping (Binder et al, 1999). Thus, while some aspects of eye movement behavior are associated with shifts in attention, the influence of leftward interword spaces that we observed in our study does not appear to rely on such shifts.…”
contrasting
confidence: 55%
“…Binder, Pollatsek, and Rayner (1999) found that changing the identity of the word to the left of the currently fixated word (and so, farther away than the widely reported leftward extent of the perceptual span) disrupted performance relative to when the word remained unchanged. In a similar vein, Rayner, Castelhano, and Yang (2009) found that performance was disrupted when the word to the left of the fixated word comprised only xs during each fixational pause, and Apel, Henderson, and Ferreira (2012) found that regression performance was disrupted when the word to the left of the fixated word was composed of replacement letters.…”
mentioning
confidence: 99%
“…In contrast, when influences of text to the left of fixation have been observed in other research, one indication is that these influences occur only with regressive saccades (Apel et al, 2012; see also Binder et al, 1999), and so may occur only when a greater allocation of attention has been made to the left of fixation prior to a saccade being made in that direction (although see Rayner et al, 2009). Thus, it seems that while some aspects of eye movement behaviors may be associated with shifts in attention, the influences of leftward letter content observed in the present study do not rely on such shifts.…”
Section: Postview Effects In Reading 21mentioning
confidence: 78%
“…The change was implemented within one screen refresh, was made during the saccade itself, and the saccade started some distance away from the critical word (cf. Binder, Pollatsek, & Rayner, 1999), so participants were unable to see the change itself (Matin, 1974).…”
Section: Methodsmentioning
confidence: 99%